Miłosz dla bibliofilów - Bahneva, Kalina (Postscriptum Polonistyczne, 2020)
The article deals with a Bulgarian translation of Czesław Miłosz’s poem Child of Europe. The author of the translation, Katia Mitova, was a wellknown interpreter of Polish literature and an expert in literature. The translation itself, which appeared in fifty numbered copies, forms a separate bibliophile edition (the illustrator of the volume was Jan Libenstein). The article discusses the aspects connected with the elitism of the edition in the context of interesting Bulgarian bibliophile tradition observed in the interwar period, but also in connection with ambiguous and difficult to understand concepts found in the poem written by the Polish Noble Prize Laureate. The author of the article focuses on the very concept of Europe as it appears in the poem and its connotations to the essence of human intelligence and cognition. Additionally, the article presents various aspects of irony regarded as a form of speech, important not only in the process of appropriate comprehension of this poetic work. In translation, it also helps to attain the correct interpretation of the ideological and artistic contents of the poem.